2020
DOI: 10.34293/education.v9i1.3384
|View full text |Cite
|
Sign up to set email alerts
|

Child Protection Policy Awareness of Teachers and Responsiveness of the School: Their Relationship and Implications

Abstract: In every institution in the country, there are countless stories of children being bullied, abused, or maltreated. This can happen inside a school or outside its premises. A child protection policy is a must to protect these children. This study assesses the child protection policy awareness of teachers and the responsiveness of the schools. It also wanted to know the relationship and program implications. The researchers used a descriptive-correlation research design with the survey as the primary data-gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…DepEd ( 2014) reiterated that the CPP's objective is to promote a zero-tolerance policy for any act of child exploitation, violence, discrimination, and other forms of abuse. The results of the present study conform to the results of previous studies that teachers are aware about the policy adopted by the DepEd in protecting the children (Asio et al, 2020;Bayucca, 2020). However, the study of Estremera (2018) found out that teachers are moderately aware about the policy.…”
Section: Teachers' Awareness Of the Child Protection Policysupporting
confidence: 90%
See 1 more Smart Citation
“…DepEd ( 2014) reiterated that the CPP's objective is to promote a zero-tolerance policy for any act of child exploitation, violence, discrimination, and other forms of abuse. The results of the present study conform to the results of previous studies that teachers are aware about the policy adopted by the DepEd in protecting the children (Asio et al, 2020;Bayucca, 2020). However, the study of Estremera (2018) found out that teachers are moderately aware about the policy.…”
Section: Teachers' Awareness Of the Child Protection Policysupporting
confidence: 90%
“…In the Philippines, extensive scholarly attention has been given to child protection. These studies focused on the analysis of policy relating to the protection of children (Roche, 2018), a systematic review of literature on child protection and maltreatment (Roche, 2017), awareness of teachers in the CPC (Asio et al, 2020;Bayucca, 2020;Estremera, 2018), perception of teachers and school heads in CPP (Baronia, 2020), compliance to CPP (Zamora & Madrigal, 2018), and preventing child maltreatment (Alampay et al, 2018). However, very little attention has been given to the teachers' awareness and attitude towards the policy.…”
Section: Child Protection Policymentioning
confidence: 99%
“…Other than teachers and staff, they are the school's guidelines, role models, directors of educational institutions, and managers of the workforce in a school. Implementing policies and programs about child protection [16] is also essential for the school to observe and, more importantly, for the school head. The school principal is the torchbearer of the values and activities of his/her institution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study found that teachers are very good in terms of professional skills . In addition, since teachers deal with different students, an article found that teachers are also aware of the protection policy intended for their students (Asio et al, 2020). Chaos in the classroom is an inevitable event that may occur anytime, regardless whether an observation is going on or not.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers and students provide different results when it comes to observation of classroom performance. Different methods show promising results and effectiveness in different subjects (Bayucca, 2020;Francisco & Celon, 2020;Sebastian, 2020;Mobo, 2018). Also, preparation in the performance is crucial for teachers (Claud, 2020) and its contextualization is vital for a stronger academic platform (Jimenez, 2020b).…”
Section: Introductionmentioning
confidence: 99%